Advances in Multimedia Modeling [electronic resources]: 13th International Multimedia Modeling Conference, MMM 2007, Singapore, January 9-12, 2007. Proceedings, Part I - International Multimedia Modelling Conference (13th : 2007 : Singapore); Cham, Tat-Jen; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
57